Molecular characterization of pathogenic OTOA gene conversions in hearing loss patients. Issue 4 (14th March 2021) - Laurent, Sacha; Gehrig, Corinne; Nouspikel, Thierry; Amr, Sami S.; Oza, Andrea; Murphy, Elissa; Vannier, Anne; Béna, Frédérique Sloan; Carminho‐Rodrigues, Maria Teresa; Blouin, Jean‐Louis; Cao Van, Hélène; Abramowicz, Marc; et al.
Abstract: Bi‐allelic loss‐of‐function variants of OTOA are a well‐known cause of moderate‐to‐severe hearing loss. Whereas non‐allelic homologous recombination‐mediated deletions of the gene are well known, gene conversions to pseudogene OTOAP1 have been reported in the literature but never fully described nor their pathogenicity assessed. Here, we report two unrelated patients with moderate hearing‐loss, who were compound heterozygotes for a converted allele and a deletion of OTOA . The conversions were initially detected through sequencing depths anomalies at the OTOA locus after exome sequencing, then confirmed with long range polymerase chain reactions. Both conversions lead to loss‐of‐function by introducing a premature stop codon in exon 22 (p.Glu787*). Using genomic alignments and long read nanopore sequencing, we found that the two probands carry stretches of converted DNA of widely different lengths (at least 9 kbp and around 900 bp, respectively).